Empowering Marginal Group during Covid-19 Pandemic: a Lesson from SIGAB and Rifka Annisa - Rahmawati, Dian Eka; Puspitasari, Chandra Dewi (Journal of Government and Civil Society, 2023)
The aim of this research is to analyze the role of NGO SIGAB and NGO Rifka Annisa in empowering people with disabilities, women and children affected by the Covid-19 pandemic. These two groups received less treatment from the government during the Covid-19 pandemic due to limited government resources. This research uses qualitative methods with data collection techniques using interviews and documentation. The research results found that these two NGOs carried out an empowerment and advocacy role. Empowerment is carried out by SIGAB by collecting data to channel the aspirations of people with disabilities and providing policy input to the government, educating the public and people with disabilities about Covid-19 through media that can be accessed by people with disabilities. Meanwhile, Rifka Annisa protects and advocates for groups of women affected by COVID-19, especially those experiencing violence, while providing education. The pandemic conditions which were feared to paralyze civil society during the Covid-19 pandemic, on the contrary were able to strengthen it in a spirit of solidarity. The advantages these two NGOs have are the wide network they have built and the strong group solidarity.Tujuan penelitian ini untuk menganalisa peran LSM SIGAB dan LSM Rifka Annisa dalam pemberdayaan penyandang disabilitas, perempuan dan anak terdampak pandemi Covid-19. Kedua kelompok tersebut kurang mendapatkan penanganan dari pemerintah di masa pandemic Covid-19 karena keterbatasan sumberdaya pemerintah. Penelitian ini menggunakan metode kualitatif dengan teknik pengumpulan data menggunakan wawancara dan dokumentasi. Hasil penelitian menemukan bahwa kedua NGO ini menjalankan peran pemberdayan dan peran advokasi. Pemberdayaan dilakukan oleh SIGAB dengan mengumpulkan data untuk menyalurkan aspirasi penyandang disabilitas serta memberikan masukan kebijakan kepada pemerintah, mengedukasi masyarakat dan penyandang disabilitas tentang Covid-19 melalui media yang dapat diakses oleh penyandang disabilitas. Sedangkan Rifka Annisa melindungi dan mengadvokasi kelompok perempuan terdampak COVID-19, khususnya yang mengalami kekerasan, sekaligus memberikan pendidikan. Kondisi pandemi yang dikhawatirkan melumpuhkan civil society pada masa pandemic Covid-19, justru sebaliknya mampu menguatkannya dalam semangat solidaritas. Keunggulan yang dimiliki kedua LSM ini adalah luasnya jaringan yang mereka bangun dan soliditas kelompok yang kuat.